Role of information management lecturer towards plagiarism / Roymax Sebastian - Sebastian, Roymax (Faculty of Information Management, 2011)
Role of faculty of Information Management in UiTM Kedah is responsible to play a main role towards the plagiarism problem among the students in faculty of Information Management in UiTM Kedah. The main role that must have to be a good role in combating plagiarism is have a good attitude towards plagiarism, aware about plagiarism problem among the students, know the learning environment does the students do that causes doing plagiarism and the role of lecturer do to help their students avoid doing the plagiarism.